A flexible ferroelectric material, preparation method and application thereof
Through reaction treatment under mild conditions, flexible ferroelectric materials are prepared, which solves the problems of complex preparation process of existing ferroelectric materials and lack of amorphous materials, and achieves low energy consumption, environmental protection and high performance material preparation.
Patent Information
- Application Number
- CN202510138180.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The preparation process of existing ferroelectric materials is complex, difficult to manufacture, and lack of amorphous ferroelectric materials, making it difficult to meet the needs of industrial applications.
Flexible ferroelectric material was prepared by adding ultrapure water, polyvinyl alcohol and poly1,3 propylene glycol to the reactor, heating and cooling treatment, and adding organic mixed solution for reaction. The process is carried out under mild conditions, avoiding the adverse effects of high temperature on the material.
The low-temperature preparation of flexible ferroelectric materials is realized, energy consumption and side reactions are reduced, film formation, uniformity and mechanical properties of the materials are improved, and the advantages of environmental protection and low cost are provided.
Smart Images

Figure CN119613740B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials, and in particular to a flexible ferroelectric material, a preparation method and application thereof. Background Art
[0002] Since the first ferroelectric was invented in 1921, ferroelectrics have been widely used in military and civilian fields. Currently, there are about 1,000 materials that have been proven to have ferroelectric properties, of which only a few have application value. At the same time, the preparation process of ferroelectric materials is complex and difficult to manufacture, resulting in ferroelectric materials still being very rare and expensive.
[0003] Ferroelectric materials refer to materials that have spontaneous polarization and can be reversed by an electric field. As crystals, ferroelectric materials have three basic characteristics: 1. They have a hysteresis loop, and when the electric field is 0, the residual polarization intensity is not 0; 2. They have pyroelectricity and piezoelectricity; 3. They have a Curie temperature, at which the ferroelectric polarization phase transforms into a paraelectric phase.
[0004] The development of ferroelectric materials has gone through four periods, and has now entered the ferroelectric thin film period, and ferroelectric materials have entered the stage of miniaturization and refinement. At the same time, higher requirements have been put forward for the preparation of ferroelectric materials. Flexible polymer ferroelectric materials represented by polyvinylidene fluoride (PVDF) have received widespread attention. At present, technicians in this field generally believe that only crystalline materials with asymmetric centers can have the characteristics of ferroelectric materials and form ferroelectrics. The research on polyvinylidene fluoride is also limited to the transformation of crystal form. At present, it is urgent to explore more abundant ferroelectric materials, especially amorphous ferroelectric materials, which has become an urgent requirement in the industry. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing a flexible ferroelectric material to solve the shortcomings of the prior art, namely, the high difficulty in preparing ferroelectric materials and the lack of amorphous ferroelectric materials.
[0006] The present invention is achieved through the following technical scheme. A method for preparing a flexible ferroelectric material includes: S100, adding ultrapure water into a reactor, adding polyvinyl alcohol and poly 1,3-propylene glycol at the same time, and then heating the reactor to 80-90°C until the polyvinyl alcohol and poly 1,3-propylene glycol are completely dissolved to prepare a first mixed solution; S200, cooling the first mixed solution to 60-70°C, adding an organic mixed solution to the first mixed solution, and mixing them evenly to prepare a second mixed solution; S300, keeping the second mixed solution warm at 60-70°C for a first reaction treatment, the reaction time of the first reaction treatment is 1-2h, and after the first reaction is completed, heating the second mixed solution to 85-95°C for a second reaction treatment, the reaction time of the second reaction treatment is 2-3h; S400, after the second reaction treatment is completed, waiting for the second mixed solution to cool to room temperature.
[0007] Furthermore, the organic mixed solution in step S200 of the preparation method is obtained by mixing urea and a formaldehyde aqueous solution with a concentration of 37%.
[0008] Furthermore, the organic mixed solution in step S200 of the preparation method is obtained by mixing 1,3-propylene glycol, urea and a formaldehyde aqueous solution with a concentration of 37%.
[0009] Another aspect of the present invention provides a flexible ferroelectric material, which is prepared according to the preparation method described above.
[0010] Further, the chemical formula of the hydrogen bond chain is , where N is a nitrogen atom or a nitrogen ion; H is a hydrogen atom or a hydrogen ion; O=C is a carbonyl group; and n is the number of hydrogen bond chains or the length of the hydrogen bond chain.
[0011] Furthermore, the proton donors and proton acceptors in the hydrogen-bonded chains of flexible ferroelectric materials can be interchanged, resulting in a reversal of polarity.
[0012] Furthermore, the ferroelectric material is composed of organic compounds, including carbonyl, amino, amide, urea and ether bonds, specifically including polyvinyl alcohol, poly 1,3-propylene glycol, polymethylene urea, urea, formaldehyde and 1,3-propylene glycol.
[0013] Furthermore, the prepolymer of the ferroelectric material is water-soluble.
[0014] Furthermore, the synthesis reaction of the ferroelectric material is carried out under mild conditions, with a reaction temperature of less than 100°C and a reactant concentration of less than 10%. The mild reaction conditions are conducive to the preferential generation of linear oligomers and are also conducive to the self-assembly of hydrogen bonds.
[0015] Another aspect of the present invention provides an application of a flexible ferroelectric material in the preparation of a flexible electronic device. The flexible ferroelectric material is prepared according to the preparation method described above. The prepared flexible ferroelectric material is spin-coated on an electronic grade aluminum foil substrate for film post-processing, the thickness of the formed film is controlled within 40-50 μm, and dried in a vacuum oven at 110-120° C. for 2 hours; silver paste is spin-coated on the formed film as an electrode, and after the spin coating is completed, a 1000 v / mm DC electric field is applied at 110-120° C., polarized for 2-3 hours, and then the voltage is maintained while the temperature is cooled to room temperature to prepare an aluminum-flexible ferroelectric material-silver flexible electronic device.
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0017] 1. The preparation method of the present invention has a relatively low temperature range, and the reaction process is carried out under mild conditions, which avoids the influence of high temperature environment on thermal decomposition or structural change of materials, and helps to protect sensitive organic components. At the same time, polyvinyl alcohol (PVA) and poly 1,3-propylene glycol (PPG) are used. These two water-soluble and environmentally friendly organic materials make the whole process more environmentally friendly, and the final prepared material has better film-forming properties, uniformity and mechanical properties.
[0018] 2. Compared with some existing traditional methods, the ferroelectric material preparation method of the present invention has mild reaction conditions, an environmentally friendly solvent system, adjustable process parameters, potential low energy consumption and good material properties. It can effectively reduce costs, improve production efficiency, improve material properties and has excellent environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0020] Figure 1 This is an infrared spectrum of the flexible ferroelectric material provided in Example 1 of the present invention.
[0021] Figure 2 This is a pyroelectric coefficient-temperature curve of the flexible ferroelectric material provided in Example 1 of the present invention.
[0022] Figure 3 This is a ferroelectric hysteresis curve diagram of the flexible ferroelectric material provided in Example 2 of the present invention.
[0023] Figure 4 This is a thermoelectric potential-temperature curve diagram of the flexible ferroelectric material provided in Example 3 of the present invention.
[0024] Figure 5This is a pyroelectric current-temperature curve diagram of the flexible ferroelectric material provided in Example 4 of the present invention. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0026] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as commonly understood by those skilled in the art in the art of the present invention. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail. Regarding the "comprising", "including", "having", "containing" and the like used herein, they are all open-ended terms, that is, they mean including but not limited to. Unless the context clearly indicates otherwise, the expressions "a" and "one" used herein include plural references. The term "about" used herein means a range of ±20% of the value thereafter. In some embodiments, the term "about" means a range of ±10% of the value thereafter. In some embodiments, the term "about" means a range of ±5% of the value thereafter.
[0027] Embodiment 1,
[0028] This embodiment provides a method for preparing a flexible ferroelectric material. The existing preparation process of ferroelectric materials usually requires a high-temperature sintering process or synthesis at a relatively high temperature, which not only increases energy consumption but also may cause decomposition or performance degradation of certain components. At the same time, the existing preparation process of ferroelectric materials requires long-term high-temperature treatment, and a long reaction time may cause unnecessary side reactions or loss of material properties. The preparation method provided in this embodiment overcomes the shortcomings of the prior art, and the preparation method comprises:
[0029] Step 1: Add 200 ml of ultrapure water to a reactor equipped with a thermometer and a stirrer, add 10 g of PVA-2488 and 1 g of polypropylene glycol (PPG) (molecular weight less than 700) while stirring, and raise the temperature to 90°C until PVA and PPG are completely dissolved.
[0030] Step 2: After cooling to 60°C, add 1 ml of 1,3-propylene glycol, 6 g of urea and 2 ml of 37% formaldehyde aqueous solution, keep warm at 60°C for 2 hours, then heat to 90°C and react for 1.5 hours.
[0031] Step 3: After the reaction is completed, wait for the reactants to cool to room temperature, take out the reactants, and prepare a flexible ferroelectric material.
[0032] The prepared flexible ferroelectric material was spin-coated on an electronic grade aluminum foil substrate for film post-processing, the thickness of the formed film was controlled within 50 μm, and the film was dried in a vacuum oven at 110° C. for 3 h.
[0033] Step 4: Spin-coat silver paste on the formed film as an electrode. After the spin coating is completed, apply a DC electric field of 1000v / mm at 120°C, polarize for 3h, and then maintain the voltage while cooling the temperature to room temperature. An aluminum-flexible ferroelectric material-silver device is prepared.
[0034] The infrared spectrum of the flexible ferroelectric material prepared in this embodiment is tested. Figure 1 The aluminum-flexible ferroelectric material-silver device prepared in this embodiment was tested for pyroelectric coefficient, and the obtained pyroelectric coefficient-temperature curve is shown in FIG. Figure 2 shown.
[0035] Embodiment 2,
[0036] This embodiment provides a method for preparing a flexible ferroelectric material, the preparation method comprising:
[0037] Step 1: Add 200 ml of ultrapure water to a reactor equipped with a thermometer and a stirrer, add 10 g of PVA-2488 and 1 g of polypropylene glycol PPG while stirring, and raise the temperature to 85°C until PVA and PPG are completely dissolved.
[0038] Step 2: After cooling to 65°C, add 6 g of urea and 3 ml of 37% formaldehyde aqueous solution, keep warm at 65°C for 1 hour, then heat to 95°C and react for 2 hours.
[0039] Step 3: After the reaction is completed, wait for the reactants to cool to room temperature, take out the reactants, and prepare a flexible ferroelectric material.
[0040] The prepared flexible ferroelectric material was spin-coated on an electronic grade aluminum foil substrate for film post-processing, the thickness of the formed film was controlled within 40 μm, and dried in a vacuum oven at 120° C. for 2 h.
[0041] Step 4: Spin-coat silver paste on the formed film as an electrode. After the spin coating is completed, apply a DC electric field of 1000v / mm at 110°C, polarize for 3.5h, and then maintain the voltage while cooling the temperature to room temperature. An aluminum-flexible ferroelectric material-silver device is prepared.
[0042] Figure 3The ferroelectric hysteresis loop curve (Hysteresis Loop) of the flexible ferroelectric material prepared by this embodiment is shown, which is obtained by describing the relationship curve between the electric field (Electric field) and the electric displacement (Electric displacement).
[0043] Embodiment 3,
[0044] This embodiment provides a method for preparing a flexible ferroelectric material, the preparation method comprising:
[0045] Step 1: Add 200 ml of ultrapure water to a reactor equipped with a thermometer and a stirrer, add 10 g of PVA-2488 and 1 g of polypropylene glycol PPG while stirring, and raise the temperature to 80°C until PVA and PPG are completely dissolved.
[0046] Step 2: After cooling to 70°C, add 6g of urea and 3ml of 37% formaldehyde aqueous solution, keep warm at 70°C for 1h, then heat to 90°C and react for 2h.
[0047] Step 3: After the reaction is completed, wait for the reactants to cool to room temperature, take out the reactants, and prepare a flexible ferroelectric material.
[0048] The prepared flexible ferroelectric material was spin-coated on an electronic grade aluminum foil substrate for film post-processing, the thickness of the formed film was controlled within 40 μm, and dried in a vacuum oven at 120° C. for 2 h.
[0049] Step 4: Spin-coat silver paste on the formed film as an electrode. After the spin coating is completed, apply a DC electric field of 1000v / mm at 120°C, polarize for 3h, and then maintain the voltage while cooling the temperature to room temperature. An aluminum-flexible ferroelectric material-silver device is prepared.
[0050] Figure 4 The thermoelectric potential-temperature curve of the flexible ferroelectric material prepared by this embodiment is shown. If the polarization electric field is reversed, the measured thermoelectric potential is negative.
[0051] Embodiment 4,
[0052] This embodiment provides a method for preparing a flexible ferroelectric material, the preparation method comprising:
[0053] Step 1: Add 200 ml of ultrapure water to a reactor equipped with a thermometer and a stirrer, add 10 g of PVA-2488 and 1 g of polypropylene glycol PPG while stirring, and raise the temperature to 80°C until PVA and PPG are completely dissolved.
[0054] Step 2: After cooling to 70°C, add 6g of urea and 3ml of 37% formaldehyde aqueous solution, keep warm at 70°C for 1h, then heat to 95°C and react for 3h.
[0055] Step 3: After the reaction is completed, wait for the reactants to cool to room temperature, take out the reactants, and prepare a flexible ferroelectric material.
[0056] The prepared flexible ferroelectric material was spin-coated on an electronic grade aluminum foil substrate for film post-processing, the thickness of the formed film was controlled within 50 μm, and dried in a vacuum oven at 120° C. for 2 h.
[0057] Step 4: Spin-coat silver paste on the formed film as an electrode. After the spin coating is completed, apply a DC electric field of 1000v / mm at 110°C, polarize for 3.5h, and then maintain the voltage while cooling the temperature to room temperature. An aluminum-flexible ferroelectric material-silver device is prepared.
[0058] Figure 5 The pyroelectric current-temperature curve of the flexible ferroelectric material prepared in this embodiment is shown.
[0059] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a flexible ferroelectric material, characterized in that: The preparation method comprises: S100, adding ultrapure water into a reactor, adding polyvinyl alcohol and polypropylene glycol at the same time, and then heating the reactor to 80-90° C. until the polyvinyl alcohol and polypropylene glycol are completely dissolved, to prepare a first mixed solution; S200, cooling the first mixed solution to 60-70° C., adding the organic mixed solution to the first mixed solution, and mixing them uniformly to obtain a second mixed solution; S300, keeping the second mixed solution in an environment of 60-70°C, and performing a first reaction treatment, wherein the reaction time of the first reaction treatment is 1-2 hours, After the first reaction is completed, the second mixed solution is heated to 85-95° C. and subjected to a second reaction treatment, wherein the reaction time of the second reaction treatment is 2-3 hours; S400, after the second reaction process is completed, the second mixed solution is cooled to room temperature; The organic mixed solution in step S200 of the preparation method is obtained by mixing urea and a formaldehyde aqueous solution with a concentration of 37%. Alternatively, the organic mixed solution is obtained by mixing 1,3-propylene glycol, urea and a formaldehyde aqueous solution with a concentration of 37%.
2. A flexible ferroelectric material, characterized in that: The flexible ferroelectric material is prepared according to the preparation method as claimed in claim 1, and contains a hydrogen bond chain with the general formula of ,in, N is a nitrogen atom or a nitrogen ion; H is a hydrogen atom or a hydrogen ion; O=C is a carbonyl group; n is the number of hydrogen bond chains or the length of the hydrogen bond chain.
3. The flexible ferroelectric material according to claim 2, characterized in that: The proton donors and proton acceptors in the hydrogen bond chains of the flexible ferroelectric material can exchange with each other, triggering a reversal of polarity.
4. The flexible ferroelectric material according to claim 2, characterized in that: The ferroelectric material is composed of organic compounds, including carbonyl, amino, amide, urea and ether bonds, specifically including: Polyvinyl alcohol, polypropylene glycol, polymethylene urea, urea, formaldehyde and 1,3-propylene glycol.
5. The flexible ferroelectric material according to claim 2, characterized in that: The prepolymer of the ferroelectric material is water-soluble.
6. Application of a flexible ferroelectric material in the preparation of a flexible electronic device, characterized in that: The flexible ferroelectric material is prepared according to the preparation method as claimed in claim 1, and the specific preparation of the flexible electronic device includes the following steps: The prepared flexible ferroelectric material was spin-coated on an electronic grade aluminum foil substrate for film post-processing, the thickness of the formed film was controlled within the range of 40-50 μm, and dried in a vacuum oven at 110-120°C for 2 h; Silver paste is spin-coated on the formed film as an electrode. After the silver paste is spin-coated, a DC electric field of 1000v / mm is applied at 110-120°C for polarization for 2-3h. Then, the voltage is maintained while the temperature is cooled to room temperature to prepare an aluminum-flexible ferroelectric material-silver flexible electronic device.
Citation Information
Patent Citations
Transparent dielectric film and preparation method thereof
CN110183803A
Polyamide 1.1 as well as preparation method and application thereof
CN113121770A
Full-flexible transparent film electrode as well as preparation method and application thereof
CN113611437A